Hunting From Elevated Tree Stands: Hunters' Safety Practices and Attitudes Regarding the Use of Personal Fall Arrest Systems. (September 2014) - Vigilante, William J.; Reeves, Patrick; Lim, Raymond
This study sought to identify hunters' attitudes and practices with respect to the use of personal fall arrest systems (PFAS) when hunting from elevated stands. Hunting is a popular recreational activity in the United States (US). The use of elevated stands (e.g., treestands) provides hunters with several advantages in hunting large game animals, such as deer. However, hunting from an elevated position creates a hazard and the potential for serious injury or death should the hunter fall while climbing into or out of the stand or is positioned in the stand. Hunters in Pennsylvania were surveyed regarding their hunting practices, their attitudes regarding the use of PFAS when hunting with elevated stands, reasons why they do not always use a PFAS when hunting with an elevated stand, and their prior experience with falls from elevated hunting stands. Although the results varied based upon the hunter's activity with the stand, a majority of the hunters surveyed reported not always using PFAS and that a significant percentage of hunters never use a PFAS when hunting from an elevated stand. The survey respondents reported several reasons for not always using a PFAS, including: time, cumbersome, hinders movement, do not think about it, and difficult to use. Prior surveys involving hunters have shown comparable trends and are discussed within the paper. Suggestions for future research are discussed.